How does urbanization affect perceptions and traditional knowledge of medicinal plants? - Cecilia Arjona-García; José Blancas; Leonardo Beltrán-Rodríguez; Citlalli López Binnqüist; Hortensia Colín Bahena; Ana Isabel Moreno-Calles; José Antonio Sierra-Huelsz; Xavier López-Medellín (BMC, 2021)
Abstract Background The use and knowledge of medicinal plants play an essential role in community health in rural Mexico. Medicinal plants are part of the local heritage and provide a source of economic income. Nevertheless, knowledge of their use has declined due to factors like accelerated urbanization. Some authors have proposed that by reducing natural spaces, urbanization generates changes that impact the recognition, use, and management of natural resources. Here, we evaluate how urbanization affects the knowledge, use, and perception of medicinal plants in a Biosphere Reserve in Mexico. Methods Using a mixed methodology including quantitative and qualitative analyses, we generated a list of medicinal plants, methods of preparation, prevalence of illness, and use in two communities with different degrees of urbanization. Results A total of 217 medicinal plants were identified. The more urbanized community had greater knowledge of, and used, a larger number of introduced plant species, while the less urbanized community used and had more knowledge about wild plants. One of the factors explaining these differences was occupation, with people who work outdoors showing greater knowledge of wild plants. Conclusions Urbanization can lead to a loss of knowledge of the use and management of local wild species, with implications for the conservation of biocultural heritage. Substitution of native medicinal plants by introduced species shows disinterest and disuse in the local medicinal flora, which could be reflected in their ecosystems.